AI-Driven Journalism and Media Practice: Challenges and Prospects in Newsroom Decision-Making in Nigeria - Funmi Falobi; Joseph Ifeoluwa Joy; Margaret Solo-Anaeto; Egbayelo Oluwaseun Faith (Konfrontasi: Jurnal Kultural, Ekonomi dan Perubahan Sosial, 2026)
Artificial Intelligence (AI) has rapidly evolved into a transformative force in global journalism, reshaping newsroom practices, editorial workflows, and decision-making processes. This study examines the dynamics of AI-driven journalism in Nigeria, focusing on the challenges and prospects associated with its integration into newsroom decision-making. Drawing on secondary data from scholarly literature, industry reports, and media analyses, the paper situates AI as a socio-technical innovation that is redefining traditional gatekeeping roles and fostering a hybrid model of human–algorithm collaboration in news production. The paper identifies critical challenges hindering effective AI adoption, including infrastructural deficits, limited digital literacy among journalists, funding constraints, ethical concerns, and institutional resistance to technological change. It further highlights emerging risks related to algorithmic bias, misinformation amplification, editorial autonomy, and surveillance threats to press freedom. Anchored in Diffusion of Innovation and Technological Determinism theories, the paper argues that AI is not merely a supportive tool but a transformative agent influencing the structure and culture of Nigerian newsrooms. It concludes that sustainable integration of AI in journalism requires strategic investments in infrastructure, capacity building, and the development of ethical and regulatory frameworks. By critically examining both the constraints and potentials of AI-driven journalism, the paper contributes to ongoing discourse on the future of media practice in Nigeria and underscores the need for a balanced, human-centred approach to technological adoption in newsroom decision-making.